Perencanaan Pengelolaan Sampah Industri Kreatif dan Daur Ulang Dalam Meningkatkan Ekonomi Masyarakat dan Mengurangi Pengangguran - Asmaul Husna; Sri Wahyuni; Hakim Muttaqim; Rahma Harianti; Nova Nova (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The increase in waste is currently a very important problem, especially for the Bireuen Regency area. If the existing waste cannot be managed properly then it can cause a crucial problem. If the existing waste cannot be managed properly then it can cause a crucial problem. The research objectives of this study are to determine the planning of creative and recycling industrial waste management with the aim of increasing the community's economy and reducing unemployment in Bireuen Regency and to determine the community's response to integrated 3R waste management planning in Bireuen Regency. This type of research is qualitative research. Qualitative research is a method of conducting research that focuses on events that have a natural nature. Waste management planning is designed using the business model canvas. The results show that by using the business model canvas, the first year projection is that if waste management is carried out on a small scale, it can absorb 153 workers.